2020
DOI: 10.1016/j.isci.2020.101449
|View full text |Cite
|
Sign up to set email alerts
|

Internalization-Dependent Free Fatty Acid Receptor 2 Signaling Is Essential for Propionate-Induced Anorectic Gut Hormone Release

Abstract: Summary The ability of propionate, a short-chain fatty acid produced from the fermentation of non-digestible carbohydrates in the colon, to stimulate the release of anorectic gut hormones, such as glucagon like peptide-1 (GLP-1), is an attractive approach to enhance appetite regulation, weight management, and glycemic control. Propionate induces GLP-1 release via its G protein-coupled receptor (GPCR), free fatty acid receptor 2 (FFA2), a GPCR that activates Gαi and Gαq/11. However, how pleiotropic G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 56 publications
3
11
0
Order By: Relevance
“…Surprisingly, synthetic FFAR2/FFAR3 selective ligands could not upregulate TAS1R1 or TAS1R3 transcripts, despite their ability to activate upstream receptor signaling in EECs. This is consistent with our recent findings that endogenous SCFA and synthetic ligands have distinct activation profiles at SCFA receptors (43), and thus, potentially elicit different downstream responses. If both SCFAs and synthetic ligands activate similar upstream G-protein pathways, it remains to be determined the additional mechanisms that drive the SCFA-selective increases in gene transcription of umami taste receptors, but potentially suggests a role for ligand-induced bias signaling at FFAR2/3.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Surprisingly, synthetic FFAR2/FFAR3 selective ligands could not upregulate TAS1R1 or TAS1R3 transcripts, despite their ability to activate upstream receptor signaling in EECs. This is consistent with our recent findings that endogenous SCFA and synthetic ligands have distinct activation profiles at SCFA receptors (43), and thus, potentially elicit different downstream responses. If both SCFAs and synthetic ligands activate similar upstream G-protein pathways, it remains to be determined the additional mechanisms that drive the SCFA-selective increases in gene transcription of umami taste receptors, but potentially suggests a role for ligand-induced bias signaling at FFAR2/3.…”
Section: Discussionsupporting
confidence: 93%
“…Both FFAR2 and FFAR3 couple to Gα i/o signaling, and although FFAR2 is also a known Gα q/11 -coupled receptor, we have recently demonstrated that while synthetic selective FFAR2 ligands activate Gα q/11 signaling in EECs, SCFAs do not (43). Our data in the current study support a role for GPCR-Gα i/o signaling in mediating these changes in gene expression.…”
Section: Discussionsupporting
confidence: 77%
“…SCFAs, such as acetate and propionate, are known to increase GLP-1 secretion in the intestine, which has been proven by Tolhurst et al to be driven by enteroendocrine L cells in wild-type but not FFAR2 knock-out mice. FFAR3 is also expressed in L cells [ 98 ] and is also involved in GLP-1 release; however, FFAR2 likely plays a superior role in this process, suggesting that FFAR3 has a modulatory function [ 99 , 100 ]. In a valuable study making use of a designer receptor that is exclusively activated by designer drugs (DREADD) approach, a DREADD-FFAR2 antagonist was sufficient to block GLP-1 release in a DREADD-FFAR2 knock-in mouse model [ 101 ].…”
Section: Free Fatty Acid Receptors 2 and 3 (Ffar2 And Ffar3)mentioning
confidence: 99%
“…This pathway, however, also involved Gq proteins as the selective Gq protein inhibitor YM-254890 partially inhibited GLP-1 release. In fact, Gq protein inhibition partially inhibited cAMP decreases mediated by propionate in an FFAR2-dependent but FFAR3-independent fashion, providing evidence of a role of FFAR2 as a spatiotemporal controller of a concerted Gi/q signaling network [ 100 ]. The involvement of Gq proteins in the control of the Gαi/o-βγ-PLC pathway toward intracellular calcium rise has recently been described by the Kostenis group [ 102 ].…”
Section: Free Fatty Acid Receptors 2 and 3 (Ffar2 And Ffar3)mentioning
confidence: 99%
See 1 more Smart Citation